Návrh marketingové komunikace bakalářského studijního programu - Gál, Patrik (Vysoké učení technické v Brně. Fakulta podnikatelská, 2022)
Bakalářská práce se zabývá návrhem marketingové komunikace bakalářského studijního programu Procesní management Fakulty podnikatelské Vysokého učení technického v Brně. Práce je rozdělena do tří hlavních oblastí. Teoretická část přibližuje jednotlivé pojmy z marketingu a výzkumnou metodu focus group. Analytická část se zaměřuje na poznání současného stavu a na základě výstupů z jednotlivých analýz jsou v poslední části práce vypracovány návrhy na zlepšení marketingové komunikace studijního programu.

This bachelor thesis focuses on the proposal of marketing communication of the bachelor’s study program Process Management taught at Brno University of Technology Faculty of Business and Management. The thesis is divided to three main parts. The theoretical part describes individual knowledge of marketing and the focus group research method. The analytical part focuses on describing the current state and final proposals of marketing communication of the study program are based on previous analysis outputs.
Proposal of Marketing Communication of the Bachelor's Study Program
Keywords: marketing; marketingová komunikace; online marketing; event marketing; focus group; studijní program; marketing; marketing communication; online marketing; event marketing; focus group; study program